Study of brain network alternations in non-lesional epilepsy patients by BOLD-fMRI - Li, Zhisen; Hou, Xiaoxia; Lu, Yanli; Zhao, Huimin; Wang, Meixia; Xu, Bo; Shi, Qianru; Gui, Qian; Wu, Guanhui; Shen, Mingqiang; Zhu, Wei; Xu, Qinrong; et al. (Frontiers in Neuroscience, 2023)
Objective To investigate the changes of brain network in epilepsy patients without intracranial lesions under resting conditions. Methods Twenty-six non-lesional epilepstic patients and 42 normal controls were enrolled for BOLD-fMRI examination. The differences in brain network topological characteristics and functional network connectivity between the epilepsy group and the healthy controls were compared using graph theory analysis and independent component analysis. Results The area under the curve for local efficiency was significantly lower in the epilepsy patients compared with healthy controls, while there were no differences in global indicators. Patients with epilepsy had higher functional connectivity in 4 connected components than healthy controls (orbital superior frontal gyrus and medial superior frontal gyrus, medial superior frontal gyrus and angular gyrus, superior parietal gyrus and paracentral lobule, lingual gyrus and thalamus). In addition, functional connectivity was enhanced in the default mode network, frontoparietal network, dorsal attention network, sensorimotor network and auditory network in the epilepsy group. Conclusion The topological characteristics and functional connectivity of brain networks are changed in in non-lesional epilepsy patients. Abnormal functional connectivity may suggest reduced brain efficiency in epilepsy patients and also may be a compensatory response to brain function early at earlier stages of the disease.